2023
DOI: 10.3390/su15118631
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Churn Modeling for Sustainable Business in the Telecommunication Industry: Optimized Weighted Ensemble Machine Learning

Wee How Khoh,
Ying Han Pang,
Shih Yin Ooi
et al.

Abstract: Customers are prominent resources in every business for its sustainability. Therefore, predicting customer churn is significant for reducing churn, particularly in the high-churn-rate telecommunications business. To identify customers at risk of churning, tactical marketing actions can be strategized to raise the likelihood of the churn-probable customers remaining as customers. This might provide a corporation with significant savings. Hence, in this work, a churn prediction system is developed to assist tele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…However, some studies suggest that XGBoost can be used in combination with other ensemble methods for achieving state-of-the-art performance [27]. In addition, Khoh et al [28] have proposed an optimized weighted soft voting ensemble learning model, shown through empirical results to have higher prediction accuracy than machine learning and deep learning models, among others, for customer churn prediction systems. Algorithmic optimization methods were also utilized by Vani Haridasan et al [29], who employed an arithmetic optimization algorithm (AOA) in conjunction with a stacked bidirectional long short-term memory (SBLSTM) model, demonstrating potential in performance compared to recent approaches.…”
Section: Literature Review Of Customers Churn Prediction Methodsmentioning
confidence: 99%
“…However, some studies suggest that XGBoost can be used in combination with other ensemble methods for achieving state-of-the-art performance [27]. In addition, Khoh et al [28] have proposed an optimized weighted soft voting ensemble learning model, shown through empirical results to have higher prediction accuracy than machine learning and deep learning models, among others, for customer churn prediction systems. Algorithmic optimization methods were also utilized by Vani Haridasan et al [29], who employed an arithmetic optimization algorithm (AOA) in conjunction with a stacked bidirectional long short-term memory (SBLSTM) model, demonstrating potential in performance compared to recent approaches.…”
Section: Literature Review Of Customers Churn Prediction Methodsmentioning
confidence: 99%